PENGARUH KUALITAS LAYANAN, NILAI PRODUK, KEPERCAYAAN TERHADAP NIAT UNTUK BERTRANSAKSI ULANG DENGAN KEPUASAN ANGGOTA SEBAGAI MEDIASI PADA KOSPIN âJASAâ CABANG BATANG - Ahmad Nur Rochman, 10.05.51.0018 (Students Journal of Economic and Management, 2014)
This study is a study that examines the effect of the service , product value and trust in the intentions to transact again with satisfaction as a member of the mediation services Kospin branch stems , to encourage members to transact ualang need to improve the quality of service , product value , trust and satisfaction of members . In this study , researchers used pusposive sampling and obtain a sample size of 100 sample members . Data from the questionnaire were then tested with test validity , The reliability , hypothesis , and multiple regression . The result variable service quality , product value and belief effect on customer satisfaction and service quality , product value and belief effect on intentions to transact again . Analisia further use mediation test vector that mediating variables influence the intention to transact again . The final conclusion of this study can be recommended as an input to management . Researchers believe bahawa kulaitas approach through service , product value , the trust will make members feel satisfied and will increase the members to transact again . This study has limitations that sampling periods were relatively short , not paying particular attention among variables and have not noticed any questions apkah known by members . Therefore, further studies are suggested to consider the time in the sampling periodandpay . Keywords : Quality Service, Product Value, Trust, Satisfaction and Intent Transaction Re- Member